Effect of Palm Fiber-Hydrated Lime Composition on the Permeability of Stabilised Sandy Soil - Md Yusof, Zeety; Zainorabidin, Adnan; Osman Suliman, Mohamed Awad; Omar Abu Osba, Osama Emad (International Journal of Sustainable Construction Engineering and Technology, 2023)
Sandy soil is one of the most conventional construction materials used as backfill materials in the retention of structures in foundations. This study to investigate the composition of admixture permeability experimental to stabilized sandy soil use the composition percentage (4, 6, & 8% hydrated lime only), sandy soil with 2% hydrated lime (0.5%, 1%, and 1.5% palm fiber) and 6% of hydrated lime (0.5%, 1% and 1.5% of palm fiber) proportionally. The results presented that the mixture of 2% and 6% hydrated lime with 0.5%, 1%, and 1.5% of palm fiber proportionally, decreased the percentage of reduction of permeability from 94.22% at 0 days to 66.67% at 7 days. The mixture of 6% of hydrated lime and 1.5% of palm fiber at 0 dan 7 curing time give a better performance. Thus, this helps in using the constant head method in Geotechnical practices.